Acute stress responses after indirect exposure to the MH17 airplane crash. (18th November 2018) - Jeronimus, Bertus F.; Snippe, Evelien; Emerencia, Ando C.; de Jonge, Peter; Bos, Elisabeth H.
Abstract : People can experience disasters vicariously (indirectly) via conversation, social media, radio, and television, even when not directly involved in a disaster. This study examined whether vicarious exposure to the MH17‐airplane crash in Ukraine, with 196 Dutch victims, elicited affective and somatic responses in Dutch adults about 2, 600 km away, who happened to participate in an ongoing diary study. Participants ( n  = 141) filled out a diary three times a day for 30 days on their smartphones. Within‐person changes in positive affect (PA) and negative affect (NA) and somatic symptoms after the crash were studied. Additionally, we tested whether between‐person differences in response could be explained by age, baseline personality (NEO‐FFI‐3), and media exposure. The MH17 crash elicited a small within‐person decrease in PA and an increase in NA and somatic symptoms. This response waned after 3 days and returned to baseline at day four. The decrease in PA was larger in more extraverted participants but smaller in those higher on neuroticism or conscientiousness. The NA response was smaller in elderly. Personality did not seem to moderate the NA and somatic response, and neither did media exposure. Dutch participants showed small acute somatic and affective responses up till 3 days to a disaster that they had not directly witnessed. Vicariously experienced disasters can thus elicit affective‐visceral responses indicative of acute stress reactions. Personality and age explained some of the individual differences in this reaction.